Life Cycle Assessment of fresh fish transport in Saeplast Insulated Plastic Containers - Njathi, Doreen Wanjiku, 1985- (2019)
The fishing industry in Iceland has been using plastic containers for storage and transportation of fish for decades. With a growing demand for quality fish products by the end user, an environmentally friendly option of transporting fresh fish and lower costs to the fish exporter; there has been a need to continuously improve the design of plastic containers from Saeplast. This cradle to grave LCA study was commissioned by Saeplast to assess the environmental impact of the new concept design of the 290 L twin-containers; they can be fitted into each other when stacked empty, and compare to the 460 L container. The results will be used to support decision making on design changes intended for the twin-containers. Data gathered and used was mainly from Saeplast and the ecoinvent database, and was modeled using openLCA software. The twin-containers had a higher impact on the environment compared to the 460 L container in the overall impact on the environment from transportation of fish to a market by 14%. Transport of both containers to a market without fish showed no difference in their overall impact. The twin-containers had a lower impact on the environment compared to the 460 L container when transported back empty without fish, by 33% due to a 50-60% increase in volume utilization by the twin-containers. It is recommended to reduce the weight of the container, use recycled PE in the products and switch out diesel ovens for electric ovens. Reduce, reuse and recycle for a circular economy.